Behavioral Intention Promotes Generalized Reciprocity: Evidence From the Dictator Game - Sun, Zhongqiang; Ye, Chuyuan; He, Zhihui; Yu, Wenjun (Frontiers in Psychology, 2020)
Generalized reciprocity is the phenomenon that individuals treat others in the same way that someone else treated them in the past. Besides the behavioral outcomes, whether intention information also manipulates generalized reciprocal behavior remains unclear. By conducting two rounds of the dictator game, current research investigated the influence from the dictator’s intention on the receiver’s following resource allocation performance. In the games to allocate either tokens in Experiment 1 or jobs in Experiment 2, a general tendency was shown to treat others better if being generously treated than greedily treated. Regarding to the intentionality, participants who received a generous offer (vs. greedy offer) from another person (i.e. intentional) would perform more generously to someone else. However, if the offer was randomly given by a computer program (i.e. unintentional), the way of being treated before became somewhat irrelevant to the participants’ generalized reciprocal behaviors. Those findings verify influence of the manipulation of intention on generalized reciprocity, and provide enlightenment for promoting friendly social interactions.